Uzbekistan and Malaysia: partners in nurturing global peace and well- being - Abd Rahman, Shukran (Human Assistance & Development International Inc. (HADI Inc.), 2025)
At a time when the international community is struggling with war, inequality, and environmental crises, the voices of leaders who consistently champion peace, justice, and human dignity stand out with clarity. Among them are President Shavkat Mirziyoyev of Uzbekistan and Prime Minister Anwar Ibrahim of Malaysia, both of whom underscore their countries' commitment to building a more just and peaceful world. President Shavkat Mirziyoyev and Prime Minister Anwar Ibrahim have both outlined the commitment of the two countries to supporting peace initiatives at global stage, highlighting that peace is inseparable from human well-being. Their speeches in many platforms converged on several key themes, especially the urgency of dialogue and cooperation, the reform of global institutions to better serve developing nations, and the necessity of sustainable development anchored in fairness.